Road Development Planning Meeting in Banua Anyar Urban Village, East Banjarmasin Sub-District, Banjarmasin City - Yandi Gunawan; Irawanto; Bakhtiar; Muhammad Jamili; Akhmad Ridwan; Riky Welli Saputra (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze road development planning in Banua Anyar Village, East Banjarmasin Subdistrict, Banjarmasin City. It identifies constraints and obstacles during the planning meetings in Banua Anyar Subdistrict. The research uses a qualitative approach with a descriptive method. Key informants are the Banua Anyar Village Head and the Head of the Economic and Development Section. Data collected through observation, structured interviews, and documentation. The results show that road construction planning in Banua Anyar Village does not fully comply with existing regulations. Issues include incomplete public information about musrenbang schedules, limited community involvement, and selective invitation to meetings. Facilitators' skills in guiding discussions were also rated poorly. Constraints involve inadequate facilities and places for road construction planning, and sub-optimal human resources from the sub-district and other agencies. This hinders the optimal implementation of Musrenbang according to statutory regulations. To improve, address these shortcomings, and enhance facilitators' skills. Additionally, allocate better resources and infrastructure to ensure effective road development planning in Banua Anyar Village, Banjarmasin City